Kemampuan Matematika Anak Usia 5-6 Tahun di Kober Al-Hidayah Kecamatan Cikoneng Kabupaten Ciamis - Sumardi, Sumardi; Nur, Lutfi; Sa’diyyah, Hilma Halimatus (JURNAL PAUD AGAPEDIA, 2017)
This research is motivated by the theory of mathematics learning in early childhood which has two main areas of numbers and geometry, so the researcher focuses this research on two fields. The research is a descriptive study on the mathematical ability of children aged 5-6 years in Kober Al-Hidayah Cikoneng subdistrict Ciamis regency. The purpose of this study is to describe the level of mathematical ability such as describe the ability to recognize numbers in the cardinal and ordinal, and the ability to recognize the shape of 2 dimensional geometry and 3 dimensions. The approach of research method used is quantitative method with the aim to test the theory about variable Mathematical ability in children aged 5-6 years. The research method used is survey method. The stages of this research are: 1) conducting preliminary study and problem identification. 2) data collection phase. 3) data analysis as the answer to the problem. 4) conclusion. The sample used is a saturated sample of 17 children. Data collection tools are test and observation sheet. The result of this research that 1) the mathematics ability of children aged 5-6 years in Kober Al-Hidayah Cikoneng sub-district of Ciamis Regency included in the criteria develop as expected with percentage 74,26% from total of all children, 2) ability to know cardinal number of child age 5 -6 years in Kober Al-Hidayah Cikoneng subdistrict Ciamis regency has a percentage of 94.11% of the total of all children, and the ability to recognize ordinal numbers has a percentage of 69.11% of the total of all children, and 3) the ability to recognize 2 dimensional geometry Children aged 5-6 years in Kober Al-Hidayah Cikoneng subdistrict Ciamis regency has a percentage of 70.58% of the total of all children, while the ability of 3-dimensional geometry has a percentage of 57.35% of the total of all children.Penelitian ini dilatarbelakangi oleh adanya teori tentang pembelajaran matematika pada anak usia dini yang memiliki dua bidang utama yaitu angka dan geometri, sehingga peneliti memfokuskan penelitian ini pada dua bidang tersebut. Penelitian yang dilakukan merupakan penelitian deskriptif terhadap kemampuan matematika anak usia 5-6 tahun di Kober Al-Hidayah Kecamatan Cikoneng Kabupaten Ciamis. Tujuan dari penelitian ini yaitu untuk mendeskripsikan tingkat kemampuan matematika diantaranya mendeskripsikan kemampuan mengenal angka dalam kardinal dan ordinal, serta kemampuan mengenal bentuk geometri 2 dimensi dan 3 dimensi. Pendekatan metode penelitian yang digunakan adalah metode kuantitatif dengan tujuan untuk menguji teori tentang variabel kemampuan matematika pada anak usia 5-6 tahun. Metode penelitian yang digunakan adalah metode survey. Tahapan penelitian ini yaitu : 1) melakukan studi pendahuluan dan identifikasi masalah. 2) tahap pengumpulan data. 3) analisis data sebagai jawaban dari masalah. 4) kesimpulan. Sampel yang digunakan ialah sampel jenuh yang berjumlah 17 anak. Alat pengumpulan data berupa tes dan lembar observasi. Hasil dari penelitian ini bahwa 1) kemampuan matematika anak usia 5-6 tahun di Kober Al-Hidayah Kecamatan Cikoneng Kabupaten Ciamis termasuk dalam kriteria berkembang sesuai harapan dengan persentase 74,26% dari total seluruh anak, 2) kemampuan mengenal angka kardinal anak usia 5-6 tahun di Kober Al-Hidayah Kecamatan Cikoneng Kabupaten Ciamis memiliki persentase sebanyak 94,11% dari total seluruh anak, dan pada kemampuan mengenal angka ordinal memiliki persentase sebanyak 69,11% dari total seluruh anak, dan 3) kemampuan mengenal geometri 2 dimensi anak usia 5-6 tahun di Kober Al-Hidayah Kecamatan Cikoneng Kabupaten Ciamis memiliki persentase sebanyak 70,58% dari total seluruh anak, sedangkan pada kemampuan geometri 3 dimensi memiliki persentase sebanyak 57,35% dari total seluruh anak.